P201 Medicopsis romeroi: an emerging cause of subcutaneous infections. (20th September 2022) - Gudisa, Rajendra; Kaur, Harsimran; Gupta, Parakriti; Gupta, Sunita; Ahmed, Haseen; Capoor, Malini; Marak, Rungmei; P., Madhurima; Sahu, Sunita; Wanjare, Shashi; Hallur, Vinaykumar; Bala, Uma; et al.
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objective: Medicopsis romeroi is one of the emerging dematiaceous fungi implicated in subcutaneous human infections. Despite advances in diagnostics, identification of this agent still remains delinquent owing to poor sporulation necessitating molecular modalities. Data on clinical and management profile of M. romeroi are available as case reports. In the present study, we describe an index case of M. romeroi infection and clinical risk factors and management profile of 74 cases of M. romeroi cases from India ( n  = 32) and those reported in the literature ( n  = 42) till date. Methods: A detailed history was obtained from the index patient after informed consent. Aspirated fluid was subjected to microbiological investigations. Identification of isolate was done by molecular technique using Sanger's sequencing. All isolates stored at the National culture collection of pathogenic fungi as M. romeroi were retrieved and identity confirmed by ITS sequencing. Demographic and management details were retrieved. We also conducted a systematic literature review of M. romeroi, as per PRISMA guidelines (Fig. 1). Results: Index case history: A 59-years-old diabetic female presented with lobulated swelling and sinuses on dorsum of the right hand for 10 months. A provisional diagnosis of mycetoma was made. Calcofluor-potassium hydroxide mount of aspiration fluid revealed dematiaceous septate hyphae and Sabouraud dextrose agar grew non-sporulating greyish black aerial mycelia after 3 days of incubation at 25°C and 37°C (Fig. 2). Molecular identification confirmed isolates as M. romeroi and patient was started on itraconazole with surgical excision. A total of 32 cases of M. romeroi infection from India were included. Mean age of patients was 47.2 years with male:female ratio of 1.3:1. Most common predisposing factors were post-renal transplant (46%) and farming (24%). All the patients presented with nodular or cystic swellings, with frequent involvement of lower limbs (56%). Most of the patients were managed using itraconazole (46%), followed by amphotericin B. All the patients except one responded well to treatment. Literature review: A total of 42 cases have been reported till date, of which 29% are from India. The mean age was 52.3 years, with male:female ratio of 1.4:1. Most common predisposing factors were post-renal transplant (28.5%) and farming/gardening (16.67%). The mean duration to infection in post-transplant cases was 3.26 years and the mean duration to diagnosis in all the cases was 31 months. The noteworthy finding was the absence of predisposing factors in 21.45% cases. A total of 62% presented with skin nodules on the foot, 21.5% on lower limbs, and 11.8% with ocular affliction. Identification was done using molecular modalities in 80% cases. A total of 34% cases were managed using both surgical excision and antifungals, whereas 21% were merely with surgical excision. Another remarkable finding was spontaneous resolution in 5% cases. Antifungals used include itraconazole (25%), followed by voriconazole (21%). MICs of all antifungals showed wide variation (0.25-8  μ g/ml for AMB). All the patients except two responded well to treatment and 3 had residual disease. Conclusion: Medicopsis romeroi is an emerging cause of subcutaneous infection in India. The present study underlines the significance of molecular tests in the identification of this dematiaceous fungus due to its poor sporulation, hindering the phenotypic characterization.